2011
DOI: 10.1007/s11596-011-0568-z
|View full text |Cite
|
Sign up to set email alerts
|

The elevated expression of osteopontin and NF-κB in human aortic aneurysms and its implication

Abstract: The expression and significance of osteopontin (OPN) and NF-κB in patients with thoracic aortic aneurysm (TAA) and abdominal aortic aneurysm (AAA) were investigated. Thirteen TAA specimens, 20 AAA specimens and 6 normal aortic specimens were collected. The expression of OPN, nuclear factor-κB P65 (NF-κB P65), urokinase plasminogen activator (uPA), matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase-9 (MMP-9) were detected by using immunohistochemistry and Western blotting was employed to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 22 publications
0
23
1
Order By: Relevance
“…MMPs degrade extracellular matrix proteins including collagen and elastin, and their expression has been studied widely in relation to AAA. This study found no difference in circulating MMP‐2 levels in patients with AAA compared with controls ( P = 0·590), whereas several studies reported that aortic tissue MMP‐2 was increased in patients with AAA. Circulating MMP‐9 levels were significantly increased in patients with AAA ( P = 0·002), a finding supported by many aortic tissue MMP‐9 studies.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…MMPs degrade extracellular matrix proteins including collagen and elastin, and their expression has been studied widely in relation to AAA. This study found no difference in circulating MMP‐2 levels in patients with AAA compared with controls ( P = 0·590), whereas several studies reported that aortic tissue MMP‐2 was increased in patients with AAA. Circulating MMP‐9 levels were significantly increased in patients with AAA ( P = 0·002), a finding supported by many aortic tissue MMP‐9 studies.…”
Section: Discussioncontrasting
confidence: 80%
“…S1 , supporting information). This is in contrast to aortic tissue MMP‐2 levels, which were significantly increased in six studies, with no difference in only one. Circulating MMP‐2 activity was measured by zymography in two studies, and demonstrated no difference.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations